ADVERSE DRUG REACTION REPORTS IN MALAYSIA: COMPARISON OF CAUSALITY ASSESSMENTS - HOE SEE LEI; AB FATAH AB RAHMAN; ABIDA HAQ SYED M. HAQ (Malaysian Journal of Pharmaceutical Sciences, 2007)
Causality assessment of reported adverse drug reactions (ADR) is an important component of pharmacovigilance as they contribute to better evaluation of the risk-benefit profile of drugs. The main objective of the present study was to evaluate the agreement of causality assessments of ADR between the spontaneous ADR reporters, the expert panel and the Naranjo algorithm. We retrospectively reviewed ADR reports received by the Malaysian Adverse Drug Reactions Advisory Committee (MADRAC) between January to June 2003. Causality assessments were categorized as Certain, Probable, Possible, Unlikely and Unclassifiable. A total of 384 reports were included. Spontaneous reporters assessed 30.4% as Certain, 46.1% as Probable, 21.9% as Possible and 1.6% as Unlikely. MADRAC panel assessed 21.9%, 13.0%, 64.6% and 0.5% as Certain, Probable, Possible and Unlikely, respectively. Using the algorithm, 16.4%, 83.1% and 0.5% were categorized as Probable, Possible and Unlikely, respectively. No reports achieved the Certain/Definite category using the algorithm. The total percentage of agreement between spontaneous reporters, MADRAC and Naranjo’s algorithm in causality assessment was 15.1%. Among the three groups, no agreement was found in the Certain and Unlikely categories. Spontaneous reporters attributed a higher level of causality compared to MADRAC and Naranjo’s algorithm. The difference in aims and methods in causality assessment among the three methods of assessment could be the main reason of disagreement.